Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-13T19:22:10+02:00
A)f(x)=0 <-> 0=x-4
x=4
b) f(x)=0 <->2x+1/2=0
2x=-1/2
x=-1/4
c) f(x)=0 <-> 3x+6=0
3x=-6
x=-2
d) f(x)=0 <->-0,5-4=0
-4,5=0 => brak miejsc zerowych
2009-09-13T19:31:27+02:00
Y=x-4
x=4
y=2x+0,5
x=-1/4
c)y3x+6
x=-2
y=-0,5-4 brak miejsc zerowych
2009-09-13T22:15:46+02:00
A) y=x-4
y=0
0=x-4
x-4=0
x=-4
b) y=2x+0,5 (za pomocą wzoru)
x0=-b/a (b jest licznikiem,a mianownikiem)
x0=-0,5/2
x0=-¼ (po skróceniu)
c) y=3x+6
x0=-b/a
x0=-6/3
x0=-2
d) y=-0,5-4
brak miejsc zerowych.